Chlorophyll fluorescence as a marker for herbicide mechanisms of action - Dayan, Franck E.; Zaccaro, Maria Leticia de M. [UNESP] (Academic Press Inc. Elsevier B.V., 2012)
Photosynthesis is the single most important source of 02 and organic chemical energy necessary to support all non-autotrophic life forms. Plants compartmentalize this elaborate biochemical process within chloroplasts in order to safely harness the power of solar energy and convert it into usable chemical units. Stresses (biotic or abiotic) that challenge the integrity of the plant cell are likely to affect photosynthesis and alter chlorophyll fluorescence. A simple three-step assay was developed to test selected herbicides representative of the known herbicide mechanisms of action and a number of natural phytotoxins to determine their effect on photosynthesis as measured by chlorophyll fluorescence. The most active compounds were those interacting directly with photosynthesis (inhibitors of photosystem I and II), those inhibiting carotenoid synthesis, and those with mechanisms of action generating reactive oxygen species and lipid peroxidation (uncouplers and inhibitors of protoporphyrinogen oxidase). Other active compounds targeted lipids (very-long-chain fatty acid synthase and removal of cuticular waxes). Therefore, induced chlorophyll fluorescence is a good biomarker to help identify certain herbicide modes of action and their dependence on light for bioactivity. Published by Elsevier B.V.
Keywords: Photosynthesis; Induced chlorophyll fluorescence; Photosynthetic electron rate; Mode of action; Herbicide; Mechanism of action; Light-dependent; Light-independent